Attacks on United Nations Peacekeeping Forces: A Violation of International Humanitarian Law (2015)
This paper raises the question as to whether the United Nations peacekeeping forces could be awarded a civilian status during the armed conflict in which they are deployed; which is important for the determination of prohibition of attacks against them.